PHYTOCHEMICAL ASSESSMENT, TOTAL PHENOLIC CONTENT, CYTOTOXIC, ANTIOXIDANT AND ANTIDIABETIC ACTIVITIES OF Hyoscyamus insanus - Shah, Muhammad Abdur Rehman; Rahmat, Khan; Ahmed, Mushtaq (Journal of the Chilean Chemical Society, 2021)
Abstract Hyoscyamus insanus (family Solanaceae) was traditionally used for treatment of asthma, relieving pain and increasing female body weight. The present projects was intended to assess the phytochemicals, total phenolic content, cytotoxic, antioxidant and antidiabetic activities of Hyoscyamus insanus leaves methanolic extract and its special fractions. After extraction, the methanolic extract was sequentially fractionated with hexane, chloroform and water followed by phytochemicals analysis of each sample. Brine shrimp lethality bioassay, Folin-Ciocalteu phenol reagent, DPPH, ABTS•+, H2O2 and α-amylase inhibition assay were employed for the assessment of cytotoxic property, total phenolic contents, antioxidant and anti-diabetic potency of methanolic extract and its fractions. Amino acids and protein, carbohydrates, flavonoids and saponins were found in the methanolic extract and aqueous fraction while chloroform fraction exhibited carbohydrates, flavonoids and saponins. The highest cytotoxic activity (80.6±1.2%) was exhibited by methanolic extract while maximum phenolic contents (21.93±1.17 mg GAE/g) were found in the chloroform fraction. The employed antioxidant assays expressed different results i.e. methanolic extract demonstrated highest 83.99%, 74.19% and 51.15% free radical scavenging characteristics in ABTS, DPPH and H2O2 assays respectively. The methanolic extract showed significant (53.44%) antidiabetic properties. The correlation of total phenolic contents with percentage antioxidant and anti-diabetic capabilities of methanolic extract and its special fractions was observed to be non-significant (P> 0.05). It is concluded that the Hyoscyamus insanus is a potential source of phenolic, cytotoxic, antioxidant and antidiabetic compounds.